Employment and prices - Norton, W. E.; Schott, Kerry E.; Sweeny, K. M. (Sydney : Reserve Bank of Australia, 1971)
This paper develops an equation to explain quarterly movements in civilian employment. it further provide a theoretical and empirical framework for employment and price indices.
asm 18/02/2019
Loans
Keywords: Labour supply; Prices; Employment (Economic theory)